ANALISIS E-WOM, ONLINE SHOPPING EXPERIENCE DAN TRUST TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN E-COMMERCE SHOPEE PADA MAHASISWA PASCASARJANA UNIVERSITAS RIAU - Kartika, Mela; Ganarsih, Raden Lestari (Jurnal Tepak Manajemen Bisnis, 2019)
This study aims to determine the effect of e-WOM, Online ShoppingExperience and Trust on Shopee E-commerce Purchasing Decisions andSatisfaction on Post-Graduate Students at the University of Riau. The totalpopulation of active graduate students of University of Riau in 2018 is 3.917students, then a purposive sampling approach is used with a sample of 165people. The results of the analysis show that e-WOM, Online ShoppingExperience and Trust has a significant effect on Shopee E-commerce PurchasingDecision and Satisfaction in Post-Graduate Students of the University of Riau.Goodness of Fit shows a value of 0.539> 0.36 GoFLarge. This shows that theindependent variable in the model is able to predict the dependent variable well.